Analisis Pendapatan dan Kelayakan Usaha Salad Buah pada Mf Dessert - Nahdiasma Kirana; Santi Yunus; Mukhtar Tallesang; Farida Millias Tuty; Rita Yunus (ManBiz: Journal of Management and Business, 2024)
Income is all income received from other parties in the form of money or goods, as well as industrial output, which is valued based on the current amount of money from these assets. Turnover is one of the company's components and the main objective in preparing the income statement. This research aims to conduct an analysis of fruit salad income at Mf Dessert. Through this careful research and comprehensive literature review, it is hoped that we can provide deeper insight into the income that contributes to Fruit Salad at Mf Dessert and provide recommendations that can help Mf Dessert businesses optimize their business potential. The method used is descriptive qualitative. The results of this research show that the average revenue from Mf Dessert is IDR 3,900,000,- per 5 months with production costs incurred of IDR 3,484,873,- per 5 months. The production costs consist of fixed costs of IDR 4,000 per 5 months and variable costs of IDR 3,435,000 per 5 months. From the results of data analysis, it was found that the income earned by fruit salad at Mf Dessert was IDR 415,127 per 5 months. Based on feasibility research on Mf Dessert (R/C Ratio), a value (R/C Ratio) of 1.22 or 1.22 > 1 was obtained, meaning that for every cost incurred Rp. 1, it produces income of Rp. 1.22 so that the revenue is greater than the capital spent. So it can be concluded that the fruit salad at Mf Dessert can be said to be profitable and worth running.